Developing English for Specific Purposes (ESP) Textbook for Pharmacy Students Using On-Line Teaching in Higher Education - Abd. Syakur; Esti Junining; M. Khusni Mubarok; Margarana (Britain International for Academic Research (BIAR) Publisher, 2020)
The purpose of this developmental research is to create ESP learning textbooks for Diploma three (D3) Pharmacy students at the Surabaya Pharmacy Academy, to determine the textbooks' feasibility, and to ascertain students' responses to the ESP textbooks. The ADDIE Research and Development (R&D) model is used in this study. This ESP textbook was created in response to the study's findings. The feasibility study of the ESP textbook reveals the following points: 1) The Diploma three (D3) Pharmacy program's material experts and lecturers assign a percentage of 53.33 percent below the range of 85.94 percent, indicating that the development of digital-based textbooks receives a